Basement-membrane heparan sulphate with high affinity for antithrombin synthesized by normal and transformed mouse mammary epithelial cells. - Pejler, G (1987)
Basement-membrane proteoglycans, biosynthetically labelled with [35S]sulphate, were isolated from normal and transformed mouse mammary epithelial cells. Proteoglycans synthesized by normal cells contained mainly heparan sulphate and, in addition, small amounts of chondroitin sulphate chains, whereas transformed cells synthesized a relatively higher proportion of chondroitin sulphate. Polysaccharide chains from transformed cells were of lower average Mr and of lower anionic charge density compared with chains isolated from the untransformed counterparts, confirming results reported previously [David & Van den Berghe (1983) J. Biol. Chem. 258, 7338-7344]. A large proportion of the chains isolated from normal cells bound with high affinity to immobilized antithrombin, and the presence of 3-O-sulphated glucosamine residues, previously identified as unique markers for the antithrombin-binding region of heparin [Lindahl, Bäckström, Thunberg & Leder (1980) Proc. Natl. Acad. Sci. U.S.A. 77, 6551-6555], could be demonstrated. A significantly lower proportion of the chains derived from transformed cells bound with high affinity to antithrombin, and a corresponding decrease in the amount of incorporated 3-O-sulphate was observed.